2021
DOI: 10.1074/jbc.ra120.015932
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and crystallographic investigations into isonitrile formation by a nonheme iron-dependent oxidase/decarboxylase

Abstract: The isonitrile moiety is found in marine sponges and some microbes, where it plays a role in processes such as virulence and metal acquisition. Until recently only one route was known for isonitrile biosynthesis, a condensation reaction that brings together a nitrogen atom of l -Trp/ l -Tyr with a carbon atom from ribulose-5-phosphate. With the discovery of ScoE, a mononuclear Fe(II) α-ketoglutarate-dependent dioxygenase from Streptomyces coeruleorubidu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…1 was proposed to be the first intermediate in the pathway based on the previously reported structure of ScoE with 1 and detection of 1 from a 13 C NMR experiment analyzing an enzymatic assay from SfaA . Our recent structures of ScoE with bound CABA further demonstrated one of the C5 hydrogen points toward the iron cofactor, suggesting that C5 was the most likely site of initial C–H activation and hydroxylation . Consistently, we observed a transient production of 1 where it was detected from a 3 h assay at 4 °C, but not from an overnight assay based on the NMR analysis, thus supporting the intermediacy of this compound (Figures S4 and S9).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…1 was proposed to be the first intermediate in the pathway based on the previously reported structure of ScoE with 1 and detection of 1 from a 13 C NMR experiment analyzing an enzymatic assay from SfaA . Our recent structures of ScoE with bound CABA further demonstrated one of the C5 hydrogen points toward the iron cofactor, suggesting that C5 was the most likely site of initial C–H activation and hydroxylation . Consistently, we observed a transient production of 1 where it was detected from a 3 h assay at 4 °C, but not from an overnight assay based on the NMR analysis, thus supporting the intermediacy of this compound (Figures S4 and S9).…”
Section: Resultsmentioning
confidence: 86%
“…We obtained several crystal structures of ScoE with and without substrates and noted an ordered water network extending from the CABA site. , Through site-directed mutagenesis, we confirmed the importance of Tyr96, Tyr97, Tyr101, and Arg195 at maintaining the hydrogen-bonding network between three ordered water molecules because alterations of these residues completely abrogated or severely compromised isonitrile formation. Several pathways to isonitrile formation were previously proposed; however, a definitive pathway with evidence for reaction intermediates remains elusive. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Crystallographic studies showed that the position of the Lys 193 residue in the ScoE appears to be dependent on whether substrate is bound or not. Thus, in the crystal structure coordinates of the resting state protein without substrate bound (6DCH pdb file) the Lys 193 side chain points away from the active site, whereas in the most recent substrate-bound structure (6XN6 pdb file [103]) it points into the active site. In particular, the Lys 193 side chain in the substrate-bound structure is seen to form a hydrogen bonding interaction with the carboxylate group of (R)-3-((carboxymethyl)amino)butanoic acid (CABA) substrate.…”
Section: Reaction Mechanism With Lys 193 Removed From the Modelmentioning
confidence: 99%
“…timescales, as we have shown in non-heme Fe(II) enzymes. [36,63] In such cases, MM dynamics for extensive sampling must be balanced with large-QM-region QM/MM geometry optimizations to quantify critical interactions [36] (e.g., covalent contributions to HBs [64]). We also recently showed [55] that while properties approach asymptotic limits slowly with increasing QM region size, the fluctuations of a property of a representative metal binding site of Zndependent DNA methyltransferase were as large as the differences between configurationally averaged values for different size QM regions.…”
Section: Configurational Sampling Challengesmentioning
confidence: 99%